Polyoxometalate-based injectable coacervate inhibits HCC metastasis after incomplete radiofrequency ablation via scavenging ROS - Meilin Yang; Die Liu; Yan Tan; Jieting Chen; Fan Yang; Chaoming Mei; Qi Zeng; Yong Lin; Dan Li (Journal of Nanobiotechnology)
Abstract Background Incomplete radiofrequency ablation (iRFA) stimulates residual hepatocellular carcinoma (HCC) metastasis, leading to a poor prognosis for patients. Therefore, it is imperative to develop an effective therapeutic strategy to prevent iRFA-induced HCC metastasis. Results Our study revealed that iRFA induced an abnormal increase in ROS levels within residual HCC, which enhanced tumor cell invasiveness and promoted macrophage M2 polarization, ultimately facilitating HCC metastasis. Molybdenum-based polyoxometalate (POM) is an excellent ROS-scavenging nanocluster, but its size is too small to be easily cleared by the kidneys, limiting its effectiveness in scavenging iRFA-induced ROS. To overcome this limitation, we synthesized an injectable POM-loaded coacervate delivery system named POM@Coa, which can sustainably scavenge iRFA-induced ROS by slowly releasing POM. POM@Coa markedly reduced HCC invasiveness, reversed macrophage polarization from M2 to M1, and promoted the infiltration and activation of CD8+ T cells, ultimately inhibiting HCC metastasis. Importantly, POM@Coa showed superior therapeutic efficacy to free POM in the absence of systemic toxicity. Conclusions POM@Coa exhibits the potential to decrease HCC invasiveness and activate anti-tumor immunity, opening up new avenues for the safe and effective treatment and prevention of HCC metastasis when combined with RFA.